The intensity of physiological and behavioral responses of horses to predator vocalizations - Janczarek, Iwona (BMC Vet Res, 2020)
BACKGROUND: Predatory attacks on horses can become a problem in some parts of the world, particularly when considering the recovering gray wolf populations. The issue studied was whether horses transformed by humans and placed in stable-pasture environments had retained their natural abilities to respond to predation risk. The objective of the study was to determine the changes in cardiac activity, cortisol concentrations, and behavior of horses in response to the vocalizations of two predators: the gray wolf (Canis lupus), which the horses of the breed studied had coevolved with but not been exposed to recently, and Arabian leopard (Panthera pardus nimr), from which the horses had been mostly isolated. In addition, we hypothesized that a higher proportion of Thoroughbred (TB) horse ancestry in the pedigree would result in higher emotional excitability in response to predator vocalizations. Nineteen horses were divided into groups of 75%, 50% and 25% TB ancestry. The auditory test conducted in a paddock comprised a 10-min prestimulus period, a 5-min stimulus period when one of the predators was heard, and a 10-min poststimulus period without any experimental stimuli. RESULTS: The increase in heart rate and saliva cortisol concentration in response to predator vocalizations indicated some level of stress in the horses. The lowered beat-to-beat intervals revealed a decrease in parasympathetic nervous system activity. The behavioral responses were less distinct than the physiological changes. The responses were more pronounced with leopard vocalizations than wolf vocalizations. CONCLUSIONS: The horses responded with weak signs of anxiety when exposed to predator vocalizations. A tendency towards a stronger internal reaction to predators in horses with a higher proportion of TB genes suggested that the response intensity was partly innate. The more pronounced response to leopard than wolf may indicate that horses are more frightened of a threatening sound from an unknown predator than one known by their ancestors. The differing response can be also due to differences in the characteristic of the predators’ vocalizations. Our findings suggested that the present-day horses’ abilities to coexist with predators are weak. Hence, humans should protect horses against predation, especially when introducing them into seminatural locations.